Design, development and deployment of a RSSI based wireless network for post disaster management - Kaundal, Vivek; Sharma, Paawan; Prateek, Manish; Chowdary, Vinay (International Journal of Engineering and Technology, 2018)
The wide spectrum of applications of wireless sensor networks in real time monitoring of disaster prone areas makes it very promising and reliable. The present work focuses on communication link establishment for the first 72 hours just after disaster, highlighting the capability of wireless sensor network especially in disaster prone area. The complete network consisting of 8 wireless nodes with integrated Xbee as a sensor to establish a communication link in between the pursuit team and trapped people. The network is deployed in Dunga Valley of Dehradun, Uttarakhand, a seismic zone with a population of more than 1 lakh. The nodes are capable of recognizing the traveler’s location whenever they are passing by the disaster prone areas. The nodes gather RSSI values along with the estimated distances of the traveler (having anchor node) from the pursuit team (having pursuit node). The system has proven its validity by tracking the trapped people in communication deprived area in Dunga Valley by doing mock drill several times. The paper reports the design of wireless network as well as deployment aspects of the nodes in such disaster prone areas.